The Evolution and Development of the Antibody Repertoire - Harry W Schroeder Jr (Frontiers Research Topics, 2015)
Although at first glance mechanisms used to create the variable domains of immunoglobulin appear to be designed to generate diversity at random, closer inspection reveals striking evolutionary constraints on the sequence and structure of these antigen receptors, suggesting that natural selection is operating to create a repertoire that anticipates or is biased towards recognition of specific antigenic properties. This Research Topics issue will be devoted to an examination of the evolution of antigen receptor sequence at the germline level, an evaluation of the repertoire in B cells from fish, pigs and human, an introduction into bioinformatics approaches to the evaluation and analysis of the repertoire as ascertained by high throughput sequencing, and a discussion of how study of the normal repertoire informs the construction or selection of in vitro antibodies for applied purposes.